STUDENTS’ GRAMMATICAL ERROR IN DELIVERING THE IMPROMPTU SPEECH - Vivi Amanda; Andri Donal (JEE (Journal of English Education), 2019)
The purpose of this research was to find out the types of grammatical errors frequently made by students in delivering the impromptu speech. The aim of learning a language is to be able to communicate in a right way. There is no a silent language knowledge, a language must be produced in words to achieve its goals in learning second or foreign language comprehending. Trough speaking, we can see how is a speaker skill in mastering a lang uage. A good speaker is who able to produce language which arranged as its rule. In speaking, appropriate sentence structure and context are very helping in order to gain listener‟s comprehending. In collecting the data, the researcher used documentation of video of impromptu speech. A method to analyze the error is called error analysis. The indicators are: (a) Morphology error (b) Syntax error. From these indicators, the researcher find out students‟ grammatical error in delivering the impromptu speech. In this research, the researcher found 127 errors in morphology. Those were 34 (14,5%) errors in noun, 77 (33%) errors in verb, 4 (2%) errors in adjective, 2 (1%) errors in adverb, 10 (4%) errors in preposition. In syntax was found 107 errors. Those were 26 (11%) errors in phrase, 33 (14%) errors in clause, 21 (9%) errors in sentence, and 27(11,5%) errors in intersentence. From the result, the researcher concluded that the most frequent grammatical error found in verb.